Is sustained breastfeeding associated with early childhood caries? - Devenish, Gemma; Scott, Jane; Begley, Andrea; Spencer, John; Thomson, Murray; Ha, Diep; Do, Loc (2019)
There is conflicting evidence of an association between breastfeeding and dental decay in very young children (early childhood caries (ECC)). While a recent systematic review and meta‐analysis reported that breastfeeding up to the age of 12 months reduced the risk of ECC, breastfeeding beyond 12 months was associated with a greater risk (Cui et al., 2017). The evidence however, is limited and inconsistent, with some studies finding an association only if breastfeeding continued beyond 18 or 24 months. Furthermore, a recent national study from Australia demonstrated that sustained breastfeeding (> 24 months) was not associated with ECC amongst children exposed to fluoridated water (Ha et al., 2019), indicating that the use of fluoridated water early in life moderated the relationship. The purpose of this presentation is to 1) critique the evidence related to breastfeeding practices and ECC; and 2) report the findings of an investigation into the effects of breastfeeding duration and night‐time breastfeeding on ECC amongst a cohort of Australian toddlers.